YouTuber Village: Digital Literacy Transformation and Economic Independence for the Tapen Village Community in Bondowoso - Abdul Jalel; Ahmad Abqoriyin Hisan (Eastasouth Institute, 2026)
Advances in information and communication technology have opened up opportunities for economic digitalization in rural areas. One notable phenomenon is the economic transformation in Tapen Village, Tapen District, Bondowoso Regency, widely known as the